Perancangan E-Diagnosa Penyakit Osteoarthritis Menggunakan Metode Ripple Down Rules Dan Naive Bayes - Telaumbanua, Firman Jaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this study was to solve the problem of optimizing the time used by rheumatology specialists in providing services to the number of patients who came for consultation in a limited time to provide information on the diagnosis of Osteoarthritis. The source of research data on the diagnosis of Osteoarthritis used in the study was obtained from a specialist in rheumatology at the Royal Prima General Hospital. The expert system in the form of Electronic-Diagnosa (E-Diagnosa) of Osteoarthritis in this study was built with Visual Basic Net 2008 and MySQL as data storage space. The expert system built by the author applies the Ripple Down Rules and Naïve Bayes methods with each different function. Ripple Down Rules serves to establish the rule as an initial diagnosis based on expert knowledge, then the Naïve Bayes method as a method of calculating the level of vitality in the form of the percentage of disease experienced by patients as a final decision based on the knowledge base formed using the Ripple Down Rules method. The results of this study are expected to be the best solution to solve the time optimization problem used by rheumatology specialists at the Royal Prima General Hospital and the theory generated in this study can be a reference for future researchers who use the same topic.